1996
DOI: 10.1001/archpsyc.1996.01830030086013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Consumption on Laboratory-Induced Panic and State Anxiety

Abstract: These findings suggest that alcohol acts acutely to reduce both panic and the anxiety surrounding panic, and they lend support to the view that drinking behavior among those with panic disorder is reinforced by this effect. We suggest that this process may contribute to the high rate at which alcohol-use disorders co-occur with panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 41 publications
(2 reference statements)
5
65
3
Order By: Relevance
“…''; ''Are you afraid of dying?''). This inventory, including the abbreviated version, has been used extensively in panic provocation studies [e.g., Kushner et al, 1996;Rassovsky et al, 2004;Schmidt et al, 1996].…”
Section: Methodsmentioning
confidence: 99%
“…''; ''Are you afraid of dying?''). This inventory, including the abbreviated version, has been used extensively in panic provocation studies [e.g., Kushner et al, 1996;Rassovsky et al, 2004;Schmidt et al, 1996].…”
Section: Methodsmentioning
confidence: 99%
“…(54) Monoamine oxidase inhibitors also reduce CO 2 reactivity. (55) It is noteworthy that consumption of alcohol diminishes CO 2 sensitivity in panic disorder patients, (56) a finding that sheds light on the high rates of alcohol abuse in panic disorder. pate completely in a matter of seconds.…”
Section: Pharmacologic Implicationsmentioning
confidence: 99%
“…The relaxing, tension-and stress-reducing, and sedating effects of alcohol in particular are well established. Short-term consumption of alcohol or benzodiazepines diminishes anxiety in patients with PD (Kushner et al 1996). Although the chronological relationship or primary-secondary distinction between the onset of anxiety symptoms and substance use varies considerably, many studies indicate that the onset of anxiety precedes substance use in many cases (Falk et al 2008;Merikangas et al 1998).…”
Section: Reasons For Comorbidity Of Anxiety Disorders and Substance Umentioning
confidence: 99%
“…Studies have found that individuals with a comorbid anxiety and substance use disorder have a poorer treatment response and outcome, have more personal and social problems and impairment and generate greater costs than other patients (Farris et al 2012;Kushner et al 1996); however, not all studies came to the same conclusions (Marquenie et al 2006).…”
Section: Prevention and Therapymentioning
confidence: 99%